Baccharis salicifolia aqueous extracts as antihelmintic treatment - María P. Saracino; Esteban Chaves; Cecilia C. Vila; Cecilia B. Dobrecky; Tomás Lombardo; Mariángeles Díaz; Rafael A. Ricco; Pablo C. Baldi; Ignacio J. Agudelo (Advances in Traditional Medicine, 2026)

Monoclonal antibody immune therapy response instrument for stratification and cost-effective personalized approaches in 3PM-guided pan cancer management - Salem Baldi; Mohammed Alnaggar; Maged AL-Mogahed; Khalil A. A. Khalil; Xianquan Zhan (EPMA Journal, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Climate change impacts on the potential global distribution of Maconellicoccus hirsutus - Iro A. Georgopoulou; Dimitrios P. Papachristos; Panagiotis G. Milonas; Sonia Alkafy Baldi; Darren J. Kriticos (Biological Invasions, 2025)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

Exploring novel circulating biomarkers for liver cancer through extracellular vesicle characterization with infrared spectroscopy and plasmonics - R. Di Santo; F. Verdelli; B. Niccolini; S. Varca; A. del Gaudio; F. Di Giacinto; M. De Spirito; M. Pea; E. Giovine; A. Notargiacomo; M. Ortolani; A. Di Gaspare; et al. (Analytica Chimica Acta, 2024)

An actor-centered, scalable land system typology for addressing biodiversity loss in the world’s tropical dry woodlands - Marie Pratzer; Patrick Meyfroidt; Marina Antongiovanni; Roxana Aragon; Germán Baldi; Stasiek Czaplicki Cabezas; Cristina A. de la Vega-Leinert; Shalini Dhyani; Jean-Christophe Diepart; Pedro David Fernandez; Stephen T. Garnett; Gregorio I. Gavier Pizarro; et al. (Global Environmental Change, 2024)

Native plant gardens support more microbial diversity and higher relative abundance of potentially beneficial taxa compared to adjacent turf grass lawns - Danielle S. Baldi; Christine E. Humphrey; John A. Kyndt; Tyler C. Moore (Urban Ecosystems, 2023)

Farm-level medicinal plants production and economic analysis in the Indian state of Punjab - Preet A. Singh; Neha Bajwa; Lakhwinder Sharma; Ashish Baldi (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Estimating genetic parameters of reproductive, carcass, and meat quality traits in Polled Nellore cattle - M. M. S. Mamede; G. J. M. Rosa; E. C. Eifert; F. B. Lopes; F. Baldi; M. F. Costa; R. D. Sainz; A. S. Carmo; A. S. Mascioli; C. U. Magnabosco (Tropical Animal Health and Production, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

Stealth invasions on the rise: rapid long-distance establishment of exotic pines in mountain grasslands of Argentina - Tomás Milani; Esteban G. Jobbágy; Martín A. Nuñez; M. Eugenia Ferrero; Germán Baldi; François P. Teste (Biological Invasions, 2020)

Nutritional evaluation of former food products (ex-food) intended for pig nutrition - C. Giromini; M. Ottoboni; M. Tretola; D. Marchis; D. Gottardo; V. Caprarulo; A. Baldi; L. Pinotti (Food Additives & Contaminants: Part A, 2017)

Seasonal differences in climate in the Chianti region of Tuscany and the relationship to vintage wine quality - Michael James Salinger; Marina Baldi; Daniele Grifoni; Greg Jones; Giorgio Bartolini; Stefano Cecchi; Gianni Messeri; Anna Dalla Marta; Simone Orlandini; Giovanni A. Dalu; Gianpiero Maracchi (International Journal of Biometeorology, 2015)

Genetic association between temperament and sexual precocity indicator traits in Nellore cattle - T. S. Valente; A. C. Sant’Anna; F. Baldi; L. G. Albuquerque; Mateus J. R. Paranhos da Costa (Journal of Applied Genetics, 2015)

Genetic parameters and investigation of genotype × environment interactions in Nellore × Hereford crossbred for resistance to cattle ticks in different regions of Brazil - D. R. Ayres; R. J. Pereira; A. A. Boligon; F. Baldi; V. M. Roso; L. G. Albuquerque (Journal of Applied Genetics, 2015)

Biochemical characterization of some cyanobacterial strains from salt marshes of the Venice Lagoon - A. A. Sfriso; D. Marchetto; M. Gallo; F. Baldi (Journal of Applied Phycology, 2014)

Computer image analysis: an additional tool for the identification of processed poultry and mammal protein containing bones - L. Pinotti; T. Fearn; S. Gulalp; A. Campagnoli; M. Ottoboni; A. Baldi; F. Cheli; G. Savoini; V. Dell’Orto (Food Additives & Contaminants: Part A, 2013)

Glycemic control influences lung membrane diffusion and oxygen saturation in exercise-trained subjects with type 1 diabetes - Courtney M. Wheatley; James C. Baldi; Nicholas A. Cassuto; William T. Foxx-Lupo; Eric M. Snyder (European Journal of Applied Physiology, 2011)

Evaluation the of PL-PG-PA system in relation to quality of bovine milk - L. Rossi; F. Galante; E. Fusi; M. Luini; V. Dell’Orto; A. Baldi (Veterinary Research Communications, 2009)

Differential composition of culture supernatants from wild-type Brucella abortus and its isogenic virB mutants - M. Victoria Delpino; Diego J. Comerci; Mary Ann Wagner; Michel Eschenbrenner; Cesar V. Mujer; Rodolfo A. Ugalde; Carlos A. Fossati; Pablo C. Baldi; Vito G. DelVecchio (Archives of Microbiology, 2009)

A hydrological onset and withdrawal index for the West African monsoon - G. A. Dalu; M. Gaetani; M. Baldi (Theoretical and Applied Climatology, 2009)

Evaluation of the damage induced by ochratoxin A and the protective role of α-tocopherol in cultured bovine mammary epithelial cells - E. Fusi; R. Rebucci; C. Pecorini; L. Rossi; F. D’Ambrosio; A. Baldi (Veterinary Research Communications, 2008)

Co-culture of arbuscular mycorrhiza-like fungi (Piriformospora indica and Sebacina vermifera) with plant cells of Linum album for enhanced production of podophyllotoxins: a first report - Ashish Baldi; Abhishek Jain; Nishant Gupta; A. K. Srivastava; V. S. Bisaria (Biotechnology Letters, 2008)

Influence of the sample collection method on salivary interleukin–6 levels in resting and post-exercise conditions - M. A. Minetto; M. Gazzoni; F. Lanfranco; M. Baldi; L. Saba; R. Pedrola; P. V. Komi; A. Rainoldi (European Journal of Applied Physiology, 2007)

Effects of Rumen-protected Choline Supplementation in Periparturient Dairy Goats - F. D’Ambrosio; A. Campagnoli; F. Susca; E. Fusi; R. Rebucci; A. Agazzi; L. Pinotti; A. Baldi (Veterinary Research Communications, 2007)

Cyclo-oxygenase-2 (COX-2) inhibition reduces apoptosis in acute myocardial infarction - A. Abbate; F. Limana; M. C. Capogrossi; D. Santini; G. G. L. Biondi-Zoccai; S. Scarpa; A. Germani; S. Straino; A. Severino; F. Vasaturo; M. Campioni; G. Liuzzo; et al. (Apoptosis, 2006)

Heterologous Expression of Biologically Active Porcine Lactoferrin in Pichia Pastoris Yeast - C. Pecorini; F. Savazzini; P. A. Martino; E. Fusi; C. Fogher; A. Baldi (Veterinary Research Communications, 2005)

Mechanisms of protection by pantoprazole against NSAID-induced gastric mucosal damage - M. Fornai; G. Natale; R. Colucci; M. Tuccori; G. Carazzina; L. Antonioli; S. Baldi; V. Lubrano; A. Abramo; C. Blandizzi; M. Del Tacca (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Iron deficiency-induced changes in carbon fixation and leaf elemental composition of sugar beet (Beta vulgaris) plants - A. D. Rombolà; Y. Gogorcena; A. Larbi; F. Morales; E. Baldi; B. Marangoni; M. Tagliavini; J. Abadía (Plant and Soil, 2005)

Analytical evaluation of mesoscale fluxes and pressure field - Marina Baldi; Giovanni A. Dalu; Roger A. Pielke; Francesco Meneguzzo (Environmental Fluid Mechanics, 2005)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Cloning and linkage mapping of resistance gene homologues in apple - P. Baldi; A. Patocchi; E. Zini; C. Toller; R. Velasco; M. Komjanc (Theoretical and Applied Genetics, 2004)

Monte Carlo Inversion of DInSAR Data for Dislocation Modeling: Application to the 1997 Umbria-Marche Seismic Sequence (Central Italy) - S. Stramondo; S. Santini; P. Baldi; M. Dragoni; A. Piombo; S. Salvi; G. Spada (Pure and Applied Geophysics, 2004)

Antigenic Recombinant Proteins Expressed in Tobacco Seeds as a Model for Edible Vaccines Against Swine Oedema - L. Rossi; A. Baldi; V. Dell'Orto; C. Fogher (Veterinary Research Communications, 2003)

Milk Choline, α-Tocopherol and Neutrophil Chemotaxis in the Periparturient Dairy Cow - L. Pinotti; R. Rebucci; E. Fusi; L. Rossi; A. Baldi (Veterinary Research Communications, 2003)

DM235 (sunifiram): a novel nootropic with potential as a cognitive enhancer - Ghelardini C.; Galeotti N.; Gualtieri F.; Romanelli M.; Bucherelli C.; Baldi E.; Bartolini A. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Chromosome regions and stress-related sequences involved in resistance to abiotic stress in Triticeae - Luigi Cattivelli; Paolo Baldi; Cristina Crosatti; Natale Di Fonzo; Primetta Faccioli; Maria Grossi; Anna M. Mastrangelo; Nicola Pecchioni; A. Michele Stanca (Plant Molecular Biology, 2002)

Modeling coseismic displacements resulting from SAR interferometry and GPS measurements during the 1997 Umbria-Marche seismic sequence - S. Salvi; S. Stramondo; M. Cocco; M. Tesauro; I. Hunstad; M. Anzidei; P. Briole; P. Baldi; E. Sansosti; G. Fornaro; R. Lanari; F. Doumaz; et al. (Journal of Seismology, 2000)

Cold-regulated gene expression during winter in frost tolerant and frost susceptible barley cultivars grown under field conditions - Elena Giorni; Cristina Crosatti; Paolo Baldi; Maria Grossi; Caterina Marè; A. Michele Stanca; Luigi Cattivelli (Euphytica, 1999)